Study of Life Events and Quality of Life in Patients of Major Depressive Disorder - Alkesh Patil; Aparna Sengupta; Ashwini Mule; Sagar Karia (Annals of Indian Psychiatry)
Background: Depression is one of the most common mental illnesses found across all ages, genders and socioeconomic status. It has significant health, psychosocial, and economic impact. It is worse than many chronic medical diseases and has a negative effect on quality of life which persists even after remission. Objectives: The aim of this research was to study the relationship of major depressive disorder with quality of life and stressful life events in adults. Materials and Methods: This was a cross-sectional study wherein purposive sampling method was employed. Patients from psychiatry outpatient department who fulfilled the criteria for major depressive disorder and belonging to the age range of 18–75 years were shortlisted and requested to participate in the study. After taking informed consent, data on quality of life, enjoyment and satisfaction, stressful life events and severity of depression were gathered using questionnaires and a semi structured interview. Results: Severity of depression was found to be negatively correlated with quality of life, enjoyment and satisfaction P = 0.001 level of significance. There were no significant correlations between severity of depression and stressful life events. Pearson’s Chi-square indicated that the severity of depression has a significant association with highest educational qualification, occupation, marital status, and socioeconomic status. Conclusion: Measuring and keeping track of quality of life through self-report levels is important in improving depressive disorders and should be integral part of management. Other steps comprise of starting early treatment, ensuring treatment adherence, reducing severity, and reducing relapse. Psychosocial interventions should also be taken into consideration.